2020
DOI: 10.1016/j.celrep.2020.107860
|View full text |Cite
|
Sign up to set email alerts
|

MAP4K Interactome Reveals STRN4 as a Key STRIPAK Complex Component in Hippo Pathway Regulation

Abstract: Highlights d Proteomic analysis defines the human MAP4K family interactome d The STRIPAK complex component STRN4 interacts with and inhibits MAP4Ks d STRN4 is a positive regulator of YAP d Elevated STRN4 expression is associated with YAP activation in endometrial cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 55 publications
1
47
0
Order By: Relevance
“…Hpo/MST12 and MAP4Ks are negatively regulated by a large protein complex called STRIPAK that brings PP2A to dephosphorylate and inhibit these kinases ( Bae et al, 2017 ; Zheng et al, 2017 ; Kim J.W. et al, 2020 ; Seo et al, 2020 ; Tang et al, 2020 ). A recent study suggests that the STRIPAK complex integrates multiple upstream signals to regulate Hippo signaling pathway ( Chen et al, 2019 ).…”
Section: Overview Of the Canonical Hippo Signaling Pathwaymentioning
confidence: 99%
“…Hpo/MST12 and MAP4Ks are negatively regulated by a large protein complex called STRIPAK that brings PP2A to dephosphorylate and inhibit these kinases ( Bae et al, 2017 ; Zheng et al, 2017 ; Kim J.W. et al, 2020 ; Seo et al, 2020 ; Tang et al, 2020 ). A recent study suggests that the STRIPAK complex integrates multiple upstream signals to regulate Hippo signaling pathway ( Chen et al, 2019 ).…”
Section: Overview Of the Canonical Hippo Signaling Pathwaymentioning
confidence: 99%
“…Different combinations of these core proteins and accessory proteins results in the formation of different STRIPAK complexes. And it was reported that the STRIPAK complex plays many important roles in embryo development, cancer, diabetes, autism, and many other diseases, and regulates many important signaling pathways and cellular processes ( Hwang and Pallas, 2014 ; Wong et al, 2014 ; Zhang et al, 2014 ; Lant et al, 2015 ; Madsen et al, 2015 ; Sakuma et al, 2015 , 2016 ; Bazzi et al, 2017 ; Chursa et al, 2017 ; Huang et al, 2017 ; Pal et al, 2017 ; Zheng et al, 2017 ; Elramli et al, 2019 ; Kuck et al, 2019 ; Tang et al, 2019 ; Rodriguez-Cupello et al, 2020 ; Seo et al, 2020 ; Stein et al, 2020 ; Xie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The STRIPAK complex, an evolutionarily conserved supramolecular complex, is involved in many important physiological processes and diseases, including embryogenesis and development ( Lant et al, 2015 ; Sakuma et al, 2015 , 2016 ; Bazzi et al, 2017 ; Pal et al, 2017 ; Zheng et al, 2017 ), type 2 diabetes ( Chursa et al, 2017 ), and cancer progression ( Wong et al, 2014 ; Zhang et al, 2014 ; Madsen et al, 2015 ; Huang et al, 2017 ; Rodriguez-Cupello et al, 2020 ). The STRIPAK complex has several different formations depending on the combinations of different, mutually exclusive accessory proteins to the STRIPAK core components ( Hwang and Pallas, 2014 ; Kuck et al, 2019 ; Rodriguez-Cupello et al, 2020 ; Seo et al, 2020 ; Stein et al, 2020 ; Xie et al, 2020 ). Several important proteins combine to form the core STRIPAK components, including a striatin family member, the PP2A A/C heterodimer, Mob3, Strip1 or Strip2, and a GCKIII kinase bound via Ccm3 ( Goudreault et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies suggest that STRIPAK might be involved in cell cycle control, cell adhesion, migration, epithelial integrity and epithelial-to-mesenchymal transition. STRN4, by inhibition of MAP4K4 kinase, is considered the key regulator inhibiting the Hippo pathway involved in asthma pathogenesis 108 . In T-cells, de ciency of MAP4K4 results in Th17 differentiation with IL-6 and IL-17 expression 109 .…”
Section: Striatin-4 (Strn4)mentioning
confidence: 99%